2013
DOI: 10.1068/p7397
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation to Uncomfortable Patterns

Abstract: Grating patterns can cause discomfort and perceptual distortions. Individuals who experience discomfort and are susceptible to these distortions generally show weaker accommodation than those who are less susceptible. We measured the accommodative response to grating patterns known to differ in the discomfort they evoke because of differences in their colour, motion or spatial frequency. The parameters known to affect discomfort and distortion had no influence on the mean or variance in the accommodative respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…19 Similarly, when the colors used in Parra and colleagues' 12 study were replotted in perceptual color space (CIE UCS), there was a linear increase in the likelihood of photoparoxysmal responses with increased chromaticity separation. 22 Together, this suggests that the sensitivity arises in cortex and not in the eye per se. For example, pink and purple have a smaller chromaticity separation than red and blue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Similarly, when the colors used in Parra and colleagues' 12 study were replotted in perceptual color space (CIE UCS), there was a linear increase in the likelihood of photoparoxysmal responses with increased chromaticity separation. 22 Together, this suggests that the sensitivity arises in cortex and not in the eye per se. For example, pink and purple have a smaller chromaticity separation than red and blue.…”
Section: Introductionmentioning
confidence: 99%
“…Larger chromaticity separations were rated as more uncomfortable to view by nonclinical populations, evoked larger hemodynamic responses, 21 and greater alpha suppression 20 in visual cortex, despite normal ocular accommodation. 22 Together, this suggests that the sensitivity arises in cortex and not in the eye per se. However, the relationship between discomfort and neural response to chromaticity separation was only linear when color difference was calculated in perceptual color space and not when calculated in terms of cone activation.…”
Section: Introductionmentioning
confidence: 99%
“…Over a large gamut of chromaticity, increasing chromaticity difference consistently increases discomfort (Haigh et al, 2012(Haigh et al, , 2013aLindquist et al, 2021), and evokes a large hemodynamic (Haigh et al, 2013a(Haigh et al, , 2015 and electrophysiological response (Haigh et al, 2015(Haigh et al, , 2019Lindquist et al, 2021). The effect is not attributable to any influence of chromatic aberration on accommodation (Haigh et al, 2013b).…”
Section: Introductionmentioning
confidence: 85%
“…With simple patterns of alternating coloured stripes, both the discomfort from the pattern and the size of the cortical response it evokes can be predicted. The discomfort is predictable not from the particular colours involved as much as from the difference between their CIE UCS 1976 chromaticities: [22][23][24][25] the greater the difference, the greater the discomfort and the greater the cortical response. 22,24 Penacchio et al 2 have shown that the same considerations apply to more complex images such as contemporary non-representational works of art.…”
Section: Colour Contrastmentioning
confidence: 99%